Third eyelid gland prolapse in a dog: Case report (Research, Society and Development, 2025)
This work aims to present a case report demonstrating the application and results of the use of exosomes containing PDRN in clinical facial aesthetics. The relevance of this study is justified by the frequent occurrence of this condition in young dogs and the need to employ surgical techniques that preserve lacrimal function and avoid recurrences. To achieve the proposed objective, a qualitative and descriptive methodology was adopted, classified as applied research, in the form of a clinical case report. Regarding technical procedures, a detailed anamnesis, complete physical and ophthalmic examination, differential diagnosis, and surgical intervention were used, followed by post-operative clinical monitoring. The study sample consisted of an eight-month-old male mixed-breed dog, treated at a veterinary clinic located in the municipality of Cacoal, State of Rondônia. The results revealed that the modified Morgan technique was effective in the anatomical repositioning of the third eyelid gland, promoting good clinical recovery, absence of recurrence, and preservation of lacrimal function, factors essential for surgical success and the animal's well-being. It is concluded, therefore, that the modified Morgan technique is a safe, efficient, and easy-to-perform alternative for the treatment of third eyelid gland prolapse in dogs, reinforcing the importance of procedures that preserve ocular physiology and reduce post-operative complications, such as keratoconjunctivitis sicca, in the practice of veterinary ophthalmology.